Validation of the anti-bacteremic efficacy of an essential oil rinse in a Brazilian population: a cross-over study - José Roberto Cortelli; Karina Cogo; Davi Romeiro Aquino; Sheila Cavalca Cortelli; Danette Ricci-Nittel; Paul Zhang; Marcelo Werneck Barata de Araujo (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This cross-over study was conducted to assess the germ-killing efficacy of an essential oil mouthrinse (EOM) by determining the blood levels of microorganisms associated with induced bacteremia and investigating the prevalence of this event in Brazilians with mild-to-moderate gingivitis. Thirty four (31.19%) subjects positive for bacteremia induced by chewing a ration of apple were enrolled out of 109 screened subjects (50 males and 59 females). A difference of at least 10 colony forming units between the pre- and post-insult blood samples was defined as a positive result. For the following two weeks patients underwent a toothbrush plus fluoride dentifrice normalization period, and were then scheduled for the Phase I protocol as follows. At baseline I, subjects were instructed to chew a new apple ration, had new blood samples taken before and after this oral stimulus, and were randomly assigned to an experimental essential oil (n = 17) or placebo (P) mouthrinse (n = 17) treatment for 2 weeks. These procedures were repeated at the end of Phase I and then followed by a two-week wash-out period (tooth brushing with fluoride dentifrice). Bacteremia was again induced at baseline and at the end of Phase II, when subjects were crossed-over to the other EOM or placebo groups. Bacterial count differences between baseline and 2-week post-treatment (EOM versus P) in the blood samples collected were assessed by analysis of covariance. Mean aerobic counts decreased by 45.8%, whereas mean anaerobic counts decreased by 63.3% after EOM treatment. After the P treatment, aerobic bacteria increased by 28.4% and anaerobic bacteria decreased by 18.5%. This study validated this novel methodology and showed that the germ-killing action of EOM significantly reduced bacteremia.